EFEK ANTIFUNGAL KITINASE AKAR SEMAI TUSAM YANG TERINFEKSI EKTOMIKORIZA (CHIT 52) TERHADAP R. SOLANI dan FUSARIUM SP. - Alfina Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
Tusam is a fast growing tree, adaptable and useful in industry. Mycorrhizal association protect tusam from root pathogen. Disease protection by mycorrhizal fungi has been associated with several mechanism, one of which, antifungal substances chitinase. However, chitinase accumulation in tusam during mycorrhizal symbiosis is not fully understand. The objective of the research was to determine the effect of chitinase antifungal activity of CHIT 52 that purified from 4 weeks age of tusam seedling root. Tusam inoculated with tusam stands soil from Kaliurang as fungi inoculate. The enzyme was purified by ammonium sulfat precipitation, dialysis, followed by gel filtration chromatography. Purified enzyme applied in R. Solani dan Fusarium sp. mycelia. The results showed that CHIT 52 can block fusarium sp. mycelia but in same enzyme concentration, CHIT 52 cannot block R. solani mycelia.